BERCERITA SEBAGAI METODE PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA INDONESIA PADA SISWA KELAS VII C DI SMPN 2 SAMBASTAHUN PELAJARAN 2023-2024 - Shahida Shahida; M. Sabiqul Huda; Aslan Aslan (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to determine and obtain information related to planning, implementation, and supporting and inhibiting factors for learning speaking skills using the storytelling method at SMPN 2 Sambas, especially class VII C. This study uses a qualitative approach with a descriptive research type. Data collection techniques use observation, interviews and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and conclusions. The data validity techniques used are source triangulation and member check. The results of the study concluded that: Planning storytelling as a method of Indonesian language speaking skills for class VII C students at SMPN 2 Sambas in the 2023-2024 academic year: first preparing a teaching module consisting of identifying learning needs and writing learning objectives, second preparing learning strategies, third preparing media and learning tools, third developing teaching materials, and preparing a learning outcome plan. Second, Implementation of storytelling as a method of Indonesian language speaking skills for class VII C students at SMPN 2 Sambas in the 2023-2024 academic year: the implementation carried out by Indonesian language teachers in learning with the storytelling method is the first by listening when the teacher shows a video, then writing what is obtained from the video, and the last is retelling based on what is listened to and writing the results of the video. Third, Supporting and inhibiting factors for storytelling as a method of Indonesian language speaking skills for class VII C students at SMPN 2 Sambas in the 2023-2024 academic year. supporting factors in learning speaking skills include motivation, student intelligence and adequate school facilities and infrastructure. While the inhibiting factors are introverted individuals, family, and community environment.